S63 Human Mesenchymal Stromal Cell (hMSC) regulation of human macrophages in in vitro models of the Acute Respiratory Distress Syndrome (ARDS). (12th November 2015) - Morrison, T; Jackson, M; Kissenpfennig, A; O'Kane, C; McAuley, D; Krasnodembskaya, A
Abstract : Background: Currently there is no effective therapy which targets the mechanisms underlying the development of ARDS. MSCs present a promising candidate therapy and are being tested in clinical trials for ARDS however their mechanisms of effect in ARDS are not fully understood. Since the alveolar macrophage is key to orchestrating the alveolar inflammatory response, it was hypothesised that hMSCs induce an anti-inflammatory M2-like phenotype in human macrophages. The aim of this study therefore was to determine the effect of MSCs on macrophage phenotype and function and to elucidate the mechanisms of these effects. Methods: Using an in vitro non-contact co-culture system, human MSCs and human monocyte-derived-macrophages (MDMs) were stimulated with E.coli lipopolysaccharide (LPS). Cytokine and marker expression profiles were examined using ELISAs, multiplex and flow cytometry. Phagocytic capacity of MDMs was measured using fluorescent E.coli bioparticles by flow cytometry. For additional clinical relevance, the ARDS microenvironment was mimicked by using bronchoalveolar lavage fluid (BALF) obtained from patients with ARDS to examine the effect of MSCs. Results: MSCs suppress the production of both pro-inflammatory and anti-inflammatory cytokines by MDMs stimulated with LPS. MSCs increase expression of M2 markers CD163 and CD206 and have no effect on M1 markers CD80 and ICAM-1. Importantly, in spite of the immunosuppressive effect on macrophages, MSCs increase their phagocytic capacity. MSC effects on cytokine secretion and marker expression were maintained in the presence of BALF from patients with ARDS (Figure 1 ). Conclusions: Human bone marrow-derived MSCs induce an M2-like phenotype and suppress cytokine secretion in primary human MDMs stimulated with LPS or ARDS patient BALF. Importantly, these effects are coupled with augmentation of macrophage phagocytosis which may be important in the clearance of bacteria and apoptotic cells. Uncovering the paracrine mechanisms responsible for the MSC effects on human macrophages remain the focus of ongoing work. Supported by: MRC MR/L017229/1, Department of Employment and Learning. Some of the materials employed in this work were provided by the Texas A&M Health Science Centre College of Medicine Institute for Regenerative Medicine at Scott and White through a grant from NCRR of the NIH, Grant # P40RR017447.